Migration and Its Alternatives among the Iban of Sarawak - Padoch, C. (Brill, 1982)
Indonesia
English
Keywords: Asian history; indonesia; Bintulu; Iban people; Longhouse; Old-growth forest; Rice; Sarawak; Shifting cultivation